Phenotypic Description and Antimicrobial Susceptibilities of Aerococcus sanguinicola Isolates from Human Clinical Samples - Facklam, Richard (American Society for Microbiology, 2003)
This report describes the clinical sources and phenotypic characterization of 16 isolates of Aerococcus sanguinicola. Sixteen conventional tests were used to describe and differentiate the 16 isolates of A. sanguinicola from 30 strains of Aerococcus viridans, 27 strains of Aerococcus urinae, and a single strain each of Aerococcus christensenii and Aerococcus urinaehominis. The phenotypic characterizations of the type strains for each species and 14 A. sanguinicola isolates were also compared in the two reference laboratories. A. sanguinicola are catalase-negative, vancomycin-susceptible, gram-positive cocci arranged in clusters and tetrads, as are all Aerococcus species except A. christensenii (which is arranged in short chains). All 16 isolates of A. sanguinicola were leucine aminopeptidase and pyrrolidonylarylamidase positive, which is unique to this species among the aerococci. All A. sanguinicola isolates grew in broth containing 6.5% NaCl, hydrolyzed hippurate, and were variable in the bile-esculin test. None of the isolates deaminated arginine or were Voges-Proskauer positive. The type strain of A. sanguinicola was isolated from a blood culture of a patient living in Denmark. Seven additional isolates were from patients living in Canada, all with urinary tract infections (six were female). Eight isolates were from patients living in five different states in the United States; five were from patients with urinary tract infections, and three were from blood cultures of one patient each with pneumonia, suspected endocarditis, and unknown clinical conditions. The antimicrobial susceptibility patterns were unremarkable; all isolates tested were susceptible to penicillin, amoxicillin, cefotaxime, cefuroxime, erythromycin, chloramphenicol, vancomycin, quinupristin-dalfopristin (Synercid), rifampin, linezolid, and tetracycline. Six of the 15 cultures were resistant to ciprofloxacin and levofloxacin, but all 15 strains were susceptible to sparfloxacin. High-level resistance was detected for meropenem (2 strains) and trimethoprim-sulfamethonazole (1 strain). Intermediate resistance was detected for trimethoprim-sulfamethoxazole (10 strains) and clindamycin (3 strains).